2011
DOI: 10.1007/s10704-011-9642-6
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model for roughness induced opening of cracks subjected to compression and shear loading

Abstract: The phenomenon of roughness induced opening or slip opening is well known in rock mechanics and relates to a crack (or rock joint) behaviour under compression and shear. It has been widely utilised in tight gas and coal bed methane industries to increase the permeability of geological reservoirs during hydraulic stimulations and has recently been extended to geothermal energy technologies for successful harnessing the thermal energy from hot rocks. However, this phenomenon is still poorly understood; and only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The second assumption uses a step function (as shown in Figure ) to express the coupling between the shear displacement and the changes in fracture aperture. The normal displacement of the fracture surfaces with respect to each other is described by virtual elastic springs spread along the fracture face (Kotousov et al ). The spring constant for a unit fracture width is calculated based on the “bed of nails” model proposed by Gangi () as κ=bΔL, where E is the Young Modulus, L is the fracture length, and b is a constant less than unity.…”
Section: Methodology For Estimation Of Shear Dilationmentioning
confidence: 99%
“…The second assumption uses a step function (as shown in Figure ) to express the coupling between the shear displacement and the changes in fracture aperture. The normal displacement of the fracture surfaces with respect to each other is described by virtual elastic springs spread along the fracture face (Kotousov et al ). The spring constant for a unit fracture width is calculated based on the “bed of nails” model proposed by Gangi () as κ=bΔL, where E is the Young Modulus, L is the fracture length, and b is a constant less than unity.…”
Section: Methodology For Estimation Of Shear Dilationmentioning
confidence: 99%
“…In addition, Salganik et al (2004) tackled an interface crack-like shear propagating in a material under compression from a mesoscopic viewpoint. Kotousov et al (2011) proposed a theoretical model to describe crack surface roughness induced by opening of a crack under mixed shear-compression loading and the stress intensity factors are found to depend on remote shear loading and roughness. Makaryan et al (2011) also analyzed a cracked elastic layer under compressive loads and found that the crack-tip field is only dominated by mode-II singularity.…”
Section: Introductionmentioning
confidence: 99%
“…The problem under consideration has many important applications in gas/oil recovery technologies associated with hydraulic stimulation of underground reservoirs (Kotousov et al 2011). These technologies can provide a significant enhancement of the permeability of geological reservoirs and often result in a considerable increase in the well productivity (Economides and Nolte 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Papanastasiou (2000) and Dam et al (2000) utilised oversimplified models to assess the residual fracture profiles but merely neglected the proppant compressibility and its distribution inside the fracture. A recent study by Kotousov (2011) deals with the final opening of two semi-infinite planes compressing a rigid circular inclusion of elastic-linear behaviour. Kotousov's work is of great practical interest in situations where the hydraulic fracture length is not known a priori and it is supported by individual particles.…”
Section: Introductionmentioning
confidence: 99%